2018
DOI: 10.1186/s12885-018-4787-6
|View full text |Cite
|
Sign up to set email alerts
|

A similar effect of P16 hydroxymethylation and true-methylation on the prediction of malignant transformation of oral epithelial dysplasia: observation from a prospective study

Abstract: BackgroundTotal P16 methylation (P16M), including P16 hydroxymethylation (P16H) and true-P16M, correlates with malignant transformation of oral epithelial dysplasia (OED). Both true-P16M and P16H are early events in carcinogenesis. The aim of this study is to prospectively determine if discrimination of true-P16M from P16H is necessary for prediction of cancer development from OEDs.MethodsPatients (n = 265) with mild or moderate OED were recruited into the double blind two-center cohort. Total-P16M and P16H we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The global 5hmC levels are decreased in cancer genomes [29,30], probably through downregulation or mutation of the TET1/2/3 genes in cancer development [33][34][35]. However, certain proportion of 5hmCs remain in some cancer or precancer tissues [23]. Recently, we found that all P16 mRNA clones in the HCT116 cells were transcribed only from the mutant P16U alleles, and none from the methylated: hydroxymethylated (M: H) P16 alleles [21], and that both true P16M and P16H could similarly increase the risk for malignant transformation of oral epithelial dysplasia in a prospective study [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global 5hmC levels are decreased in cancer genomes [29,30], probably through downregulation or mutation of the TET1/2/3 genes in cancer development [33][34][35]. However, certain proportion of 5hmCs remain in some cancer or precancer tissues [23]. Recently, we found that all P16 mRNA clones in the HCT116 cells were transcribed only from the mutant P16U alleles, and none from the methylated: hydroxymethylated (M: H) P16 alleles [21], and that both true P16M and P16H could similarly increase the risk for malignant transformation of oral epithelial dysplasia in a prospective study [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study demonstrates the presence of dense 5hmCs in the P16 exon-1 CGI in HCT116 cells, and no mRNA transcripts from the hydroxymethylated P16 (P16H) alleles were detected in the cells [21,22]. P16H was detected in 9.3% of human oral epithelial dysplasia (OED) tissues, and the malignant transformation risk was similar between P16Mpositive OED patients with and without P16H [23]. It is a fundamental question in epigenetic research to clarify whether hydroxymethylation of TSS-CGIs affects transcriptional activation of genes including P16.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that all P16 mRNA clones in the HCT116 cells were transcribed only from the unmethylated P16 alleles, and none from the methylated: hydroxymethylated (M:H) P16 alleles [21], and that both true P16M and P16H could similarly increase the risk for malignant transformation of oral epithelial dysplasia in a prospective study [23]. The findings of the present study show that the P16-TET-induced hydroxymethylation of P16 alleles in both H1299 and AGS cells retain transcriptional silence, which provides a possible mechanism to explain the above observations.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study demonstrated that there were dense 5hmCs in the P16 exon-1 CGI in HCT116 cells, and no mRNA transcripts from the hydroxymethylated P16 (P16H) alleles were detected in the cells [21,22]. P16H was detected in 9.3% of human oral epithelial dysplasia (OED) tissues [23]. However, the malignant transformation risk was similar between P16M-positive OED patients with and without P16H.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon results in fluorescence that can be detected proportionally with the amount of PCR product. For determining absolute methylation rate, two different primer sets, one for methylated and another for unmethylated DNA, are required (Liu et al, 2018).…”
Section: Dna Methylation Analysismentioning
confidence: 99%